Chromosome evolution in lycosoid spiders (Araneomorphae): a scenario based on analysis of seven species of the families Lycosidae, Senoculidae and Trechaleidae - Araujo, Douglas; Oliveira, Edson Gabriel [UNESP]; Giroti, Andre Marsola; Mattos, Viviane Fagundes [UNESP]; Paula-Neto, Emygdio [UNESP]; Brescovit, Antonio Domingos; Schneider, Marielle Cristina; Cella, Doralice Maria [UNESP] (Amer Arachnological Soc, 2015)
Within the araneomorph lineage Entelegynae, the "Higher lycosoids''("True Lycosoids''or Lycosoidea s.s.) is one of the major clades varying in its composition based on several conflicting phylogenetic hypotheses. So far, only a few species have been studied cytogenetically. In this work, the chromosomes of a senoculid spider were investigated for the first time, along with a cytogenetic analysis of six species of the families Lycosidae and Trechaleidae. Mitotic metaphase cells of the lycosid species revealed 2n male = 18 + X0 in Hogna sternalis (Bertkau 1880) and Lycosa nordenskjoldi Tullgren 1905, and 2n male = 20 + X(1)X(2)0 in Lycosa erythrognatha Lucas 1836 and Lycosa sericovittata Mello-Leitao 1939. Chromosomal analysis of the trechaleid and senoculid species showed 2n female = 22 in Neoctenus comosus Simon 1897 (Trechaleidae), and 2n male = 26 + X(1)X(2)0 in Syntrechalea syntrechaloides (Mello-Leitao 1941) (Trechaleidae) and Senoculus sp. (Senoculidae). This latter karyotype is a shared feature in most species of Lycosoidea group. The mitotic and/or meiotic cells of certain individuals of Trechaleidae exhibited one extra chromosome, which could constitute a B chromosome or represent intraspecific variability in the type of sex chromosome system. The results obtained here add new information to the discussion of the main mechanisms of chromosome evolution within this group.
Keywords: Cytogenetics; Mitosis; Meiosis; Sex chromosome system; Lycosoidea